THE COMPETITIVENESS, SPECIALIZATION, AND EXPORT PERFORMANCE OF INDONESIAN BANANA EXPORTS IN INTERNATIONAL MARKETS - Christopher Lim; Yuliawati (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
Indonesia is one of the largest banana producers in the world with high export potential, especially to Asian export destinations such as Malaysia, Japan, Singapore, and China. This study aims to analyze the competitiveness, trade specialization, and export performance of Indonesian bananas using the Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), Export Competitiveness Index (ECI), Trade Specialization Index (TSI), Comparative Export Performance (CEP), and Acceleration Ratio (AR) methods, based on UN Comtrade data for the period 2014-2023 (HS 0803). The results showed that Indonesian banana commodities globally have very weak competitiveness with an average RCA value of 0.09, although in the Malaysian market the value is quite high (3.30). The EPD value of Indonesian bananas in the Malaysian market is in the Rising Star position, Japan and Singapore in the Falling Star, and China in the Lost Opportunity. The ECI value of Indonesian bananas has an average of 1.36, indicating a strong competitive edge. ISP confirms Indonesia as an exporter country. CEP indicates that the performance of Indonesian banana exports is still relatively low, while AR indicates the ability to capture market share. To strengthen banana export competitiveness, it is necessary to improve product quality, logistics and production efficiency, and fulfillment of export standards to expand international market access.